Google's Project Nightingale highlights the necessity of data science ethics review - Christophe Olivier Schneble; Bernice Simone Elger; David Martin Shaw (EMBO Molecular Medicine)
Abstract On November 14 last year, the British Guardian published an account from an anonymous whistleblower at Google, accusing the company of misconduct in regard to handling sensitive health data. The whistleblower works for Project Nightingale, an attempt by Google to get into the lucrative US healthcare market, by storing and processing the personal medical data of up to 50 million customers of Ascension, one of America's largest healthcare providers. As the Wall Street Journal had already reported 3 days earlier, and as the whistleblower confirmed, neither was the data anonymized when transmitted from Ascension nor were patients or their doctors notified, let alone asked for consent to sharing their data with Google (Copeland, 2019; Pilkington, 2019). As a result, Google employees had full access to non‐anonymous patient health data. Google Health chief David Feinberg commented that all Google employees involved had gone through medical ethics training and were approved by Ascension (Feinberg, 2019).